Isolation and culture of adult mouse vestibular nucleus neurons - Him, Aydın; Altuntaş, Serap; Öztürk, Gürkan; Erdoğan, Ender; Cengiz, Nurettin (TUBITAK Scientific & Technical Research Council Turkey, 2017)
Background/aim: Isolated cell cultures are widely used to study neuronal properties due to their advantages. Although embryonic animals are preferred for culturing, their morphological or electrophysiological properties may not reflect adult neurons, which may be important in neurodegenerative diseases. This paper aims to develop a method for preparing isolated cell cultures of medial vestibular nucleus (MVN) from adult mice and describe its morphological and electrophysiological properties. Materials and methods: Vestibular nucleus neurons were mechanically and enzymatically isolated and cultured using a defined medium with known growth factors. Cell survival was measured with propidium iodide, and electrophysiological properties were investigated with current-clamp recording. Results: Vestibular neurons grew neurites in cultures, gaining adult-like morphological properties, and stayed viable for 3 days in culture. Adding bovine calf serum, nerve growth factor, or insulin-like growth factor into the culture medium enhanced neuronal viability. Current-clamp recording of the cultured neurons revealed tonic and phasic-type neurons with similar input resistance, resting membrane potential, action potential amplitude, and duration. Conclusion: Vestibular neurons from adult mice can be cultured, and regenerate axons in a medium containing appropriate growth factors. Culturing adult vestibular neurons provides a new method to study age-related pathologies of the vestibular system.
WOS: 000418884300035
PubMed ID: 29306256
Keywords: Vestibular Nucleus; Primary Culture; Regeneration; Mouse; Whole-Cell Recording